Domestic violence against women and girls in the state of Sergipe: a public health matter (Research, Society and Development, 2022)
Domestic violence against women is defined in the Maria da Penha Law as any action or omission based on gender that causes death, injury, physical, sexual or psychological suffering. The present study aimed to characterize the profile of domestic violence in Sergipe in the period from 2009 to 2019, through secondary data of compulsory notification. Variables related to the victim, the aggressor and the occurrence were analyzed. In the 4,997 notifications, women aged 20 to 59 years (45.0%), parda (44.8%) and with level of education between 5 and 8 years of study (13.3%) prevailed. The place of occurrence was the residence of the victim (50.8%), the aggressors were friends/acquaintances (15.6%), with recidivism rate of 29.1% and high suspicion of alcohol consumption by the aggressor (23.8%). Physical and sexual violence (53.2 and 41.6%) were highlighted; with the use of corporal force as a means of violence (44.3%) and rape, the main type of sexual violence (80.3%). The quality of reporting information is debatable since many variables are poorly filled out. The lack of precise information impairs the knowledge of the phenomenon, interfering in the actions of combat and planning of the health services, being necessary a better preparation of the professionals that deal with these situations.